Robotics and automation safety risks in construction - Earnest, G. Scott; Trout, Douglas B.; Liang, Ci-Jyun; Castleberry, Asa (Frontiers in Built Environment, 2026)
Evolving technologies such as robotics and automation have the potential to transform the American construction industry. While these technologies improve productivity and safety, they also introduce new safety risks to construction workplaces. This study conducts a scoping review to identify and analyze safety risks associated with robotics and automation in construction. Literature data was collected from the Scopus database using keywords and snowballing approaches. Following PRISMA-ScR, A total of 104 peer-reviewed articles and 33 industry and government reports between 2015 and 2025 were selected based on criteria related to construction robots and safety implications. From the literature data, robotic applications were categorized into eight groups and safety risks were categorized into four categories. A cross-cutting analysis found that mechanical and psychosocial risks dominated across all robotics and automation technologies. Risk mitigation strategies were proposed based on the analysis results. Integrating worker safety and health priorities early in the workplace transformation process, including risk mitigation strategies such as job hazard analysis, while applying the hierarchy of controls, and prevention through design strategies for each of these technologies, may help protect and enhance construction worker safety and health.